PROCESSING BREADFRUIT INTO CHIPS OF VARIOUS FLAVORS IN INCREASING STUDENT ENTREPRENEURIAL MOTIVATION - Annisya K; Sukmawati Sukmawati; Rahmatia; Tendry Ampareng; Desi Fatmala; Ali Wahyu Asshiddiq Salim; Aksyai Saputra; Samsinar Samsinar; Ilham Tahir (Sean Institute, 2023)
Utilization of breadfruit into high-quality snacks. The student creativity program – entrepreneurship (PKM-K) aims to generate student motivation to become entrepreneurs in utilizing existing natural resources into something of high quality. The methods of implementing this program are input, process (production), output, and evaluation. The results of this program are input, conducting a market survey first to find out market conditions. Then conduct a survey of breadfruit chips according to what consumers want, the final stage is the selection of materials that are not easily damaged and of high quality to be produced. Process (Production), the process of making breadfruit chips starts from the preparation of materials and tools until the breadfruit chips are ready to be marketed. The output is processed breadfruit chips which are ready to be used and marketed to consumers. The last is evaluation, namely, this stage is carried out when the production of breadfruit chips products has been completed for consumer consumption. At this stage, we will review any deficiencies that make consumers dissatisfied with the results of our products. The PKM-K conclusion program on the use of breadfruit into a high-quality snack product can provide skills to students to remain innovative and creative in managing existing natural resources, as well as provide opportunities for students to practice entrepreneurship with a comprehensive understanding of the concept of entrepreneurship, and build student enthusiasm to keep doing business.